Aplikacijski software u funkciji planiranja i upravljanja TK mrežama - Srđan Katušić (Promet - Traffic&Transportation, 1970)
This paper discusses the results of research in three different telecommunications system planning and management segments: link-up of the system control center and the outlying computer, estimate of the control center reliability and development of the algorhytm for optimization in the subscriber region. In addition the paper provides a parallel review and comparison of experiences related to the method of research in all three mentioned segments.